Philosophy of Race An Introduction - Zack, Naomi (Palgrave Philosophy Today, 2018)
Philosophy of Race: An Introduction provides plainly written access to a new subfield that has been in the background of philosophy since Plato and Aristotle. Part I provides an overview of ideas of race and ethnicity in the philosophical canon, egalitarian traditions, race in biology, and race in American and Continental Philosophy. Part II addresses race as it operates in life through colonialism and development, social constructions and institutions, racism, political philosophy, and gender. This book constructs an outline that will serve as a resource for students, nonspecialists, and general readers in thinking, talking, and writing about philosophy of race. .